Has the reaction function of the European Central Bank changed over time? - Balint Tatar (Goethe University Frankfurt, Institute for Monetary and Financial Stability (IMFS), 2023)
I have assessed changes in the monetary policy stance in the euro area since its inception by applying a Bayesian time-varying parameter framework in conjunction with the Hamiltonian Monte Carlo algorithm. I find that the estimated policy response has varied considerably over time. Most of the results suggest that the response weakened after the onset of the financial crisis and while quantitative measures were still in place, although there are also indications that the weakening of the response to the expected inflation gap may have been less pronounced. I also find that the policy response has become more forceful over the course of the recent sharp rise in inflation. Furthermore, it is essential to model the stochastic volatility relating to deviations from the policy rule as it materially influences the results.
Keywords: E52; C11; C22; C51; 330; Monetary policy rules; Bayesian time-varying parameter estimation; unconventional monetary policy; Hamiltonian Monte Carlo